Semiconductor Nanostructures for Optoelectronic Devices Processing, Characterization and Applications - Yi, Gyu-Chul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents the fabrication of optoelectronic nanodevices. The structures considered are nanowires, nanorods, hybrid semiconductor nanostructures, wide bandgap nanostructures for visible light emitters and graphene. The device applications of these structures are broadly explained. The book deals also with the characterization of semiconductor nanostructures. It appeals to researchers and graduate students.
Introduction -- Vapor-liquid-solid growth of III-V semiconductor nanowires -- III-V semiconductor nanowires on Si -- Hierarchical nanowires: Controlled growth and applications -- Wide bandgap nanostructures for visible light emitters -- Hybrid semiconductor nanostructures with graphene layers -- EXAFS characterization of semiconductor nanomaterials -- Lasing characteristics of single and assembled nanowires -- Nanophotonic device application using semiconductor nanorod heterostructures -- Semiconductor nanowire photodetectors -- AlN nanowire LEDs.
Keywords: Physics; Nanoscale science; Nanoscience; Nanostructures; Semiconductors; Optics; Optoelectronics; Plasmons (Physics).; Nanotechnology; Physics; Semiconductors; Nanotechnology and Microengineering; Nanotechnology; Optics, Optoelectronics, Plasmonics and Optical Devices; Nanoscale Science and Technology; Electronic books